Why does geography matter in big dam removal projects? Lessons from a comparison between the Sélune and Elwha River cases - Germaine, Marie-Anne; Lespez, Laurent (Frontiers in Ecology and Evolution, 2023)
The dam removal movement is resulting in numerous projects worldwide, especially in Western countries. Whether completed or in progress, these undertakings often trigger conflict. Nearly 30 years after the initiation of the first major projects, this article examines the conditions for the local appropriation of dam removal projects. From the perspective of two pioneering and emblematic projects in France (Sélune River) and the United States (Elwha River), this article highlights the geographic specificities of dam removal projects carried out in European rural areas. The aim is to discuss how to implement ambitious ecological projects without running the risk of local people losing their sensitive relationship (history, experience, landscape) with the areas once they have been restored. In other words, ecological restoration should not result in a loss of meaning and quality in the relationship between local people and newly restored spaces; it should instead enrich it. In fact, the removal of a dam is not just a technical project; it profoundly affects landscapes, disrupting uses and creating new places. We identify the modalities by which a new space is produced and appropriated by local populations based on a comparison of the relevant spaces (national park vs. rural agricultural space), the populations involved (river users, Native American tribes, residents, and NGOs), and, finally, the governance processes and interactions between expertise and politics, all to highlight the need to take geographical context into account. Based on a detailed knowledge of the formation of the Sélune dam removal project, which has been the subject of continuous participant observation since 2011, we examine these projects’ singularities and commonalities to identify the factors that contribute to their success. This study highlights the importance of the spatial scale at which the dam removal project should be framed, the role of government, and the importance of considering people’s attachment to local places. Finally, this comparison makes recommendations for improving the socio-territorial quality of ecological projects, especially in Europe, with the aim of ensuring their sustainability and success.